Let my people go surfing : the education of a reluctant businessman. Including 10 more years of business unusual - Chouinard, Yvon, ....- (New York (N.Y.) : Penguin books, 2016)
As a child, Yvon Chouinard moved to Southern California with little English and less money. Today his company, Patagonia, earns more than $600 million a year and is a beacon and benchmark for sustainable capitalism. This is the amazing story of a young man who found escape by scaling the world's highest peaks, of an innovator who used his father's blacksmith tools to fashion equipment that changed climbing forever, and of the entrepreneur who brought doing good and having a blast into the heart of a business.
Keywords: Business ; innovation